Promoting Gender Awareness through a Multicultural Approach in History Learning - Harisma, Hadianto; Darmawan, Wawan (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research is based on an awareness of the imbalance of gender representation in history teaching. For a long time, historical narratives constructed in history textbooks have often ignored women's contributions and created a limited narrative regarding the role of gender in the development of society. Indonesian historical narratives need to be reformulated through a multicultutal perspective approach to include the experiences and contributions of diverse gender groups from diverse backgrounds and cultures in the teaching of history. The purpose of this research is to strive for critical, sustainable and transformative reflection in teaching gender-aware history through a multicultural perspective. This research method uses qualitative research with a descriptive approach. The result of this research is a deep understanding and awareness of gender to students as well as knowledge of gender imbalance in Indonesian history materials.